2021
DOI: 10.1039/d1tc01628h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced guest–host interactions produce chiral conglomerates accompanying grain boundaries in a smectic phase

Abstract: Photo-induced isomerization of an azobenzene unit not only induces phase transition between two different phases but also brings marked changes of physical properties in solids and liquid crystals. We prepared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…If we design an achiral azobenzene derivative that intercalates to the adjacent layers composed of host smectic molecules, the photo-induced twist-bent structure of the guest molecule can induce chirality in the smectic phase due to the guest-host interactions in comparison to the intercalated chirality model (see Figure 10). We designed azobenzene trimer III-n (n = 7-11) and used a guest-host system of the azobenzene trimer and a host LC [89]. Their molecular structures of trimer III-n and Host LC are shown in Figure 30.…”
Section: External-field-induced Mirror Symmetry Breaking In Liquid Cr...mentioning
confidence: 99%
See 1 more Smart Citation
“…If we design an achiral azobenzene derivative that intercalates to the adjacent layers composed of host smectic molecules, the photo-induced twist-bent structure of the guest molecule can induce chirality in the smectic phase due to the guest-host interactions in comparison to the intercalated chirality model (see Figure 10). We designed azobenzene trimer III-n (n = 7-11) and used a guest-host system of the azobenzene trimer and a host LC [89]. Their molecular structures of trimer III-n and Host LC are shown in Figure 30.…”
Section: External-field-induced Mirror Symmetry Breaking In Liquid Cr...mentioning
confidence: 99%
“…Optical textures of a mixture of trimer III-11(20 wt%) and Host LC (80 wt%) cooling from the isotropic liquid with 365 nm UV irradiation at a power of 20 mW cm −2 between uncrossed polarizers. The textures are taken from ref [89]…”
mentioning
confidence: 99%
“…Therefore, applying non-equilibrium external fields might be a feasible way towards formation of chiral phases. Some recent studies have demonstrated that chiral structures could be formed under external fields, such as electric fields inducing transient chirality in designed H-shaped compounds, 35 UV irradiation inducing chiral conglomerates in the SmC phase of a binary mixture with a host smectic liquid crystal, 36 and light-controlled chirality of azophenyl liquid crystals. 37 Due to the excellent photoelectric properties of liquid crystals, 38 the research on liquid crystals under external fields may bring more advantages to form new electro-optic materials.…”
Section: Introductionmentioning
confidence: 99%